Advertising is a form of communication - Osadchyk, Oksana (My University, 2014)
Advertising is a form of communication used to influence individuals to purchase products or services or support political candidates or ideas. Frequently it communicates a message that includes the name of the product or service and how that product or service could potentially benefit the consumer. Advertising often attempts to persuade potential customers to purchase or to consume a particular brand of product or service.
Keywords: marketing; form of communication; advertising; реклама; форма общения; маркетинг; форма спілкування; кафедра економіки праці та менеджменту